If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -2(3x + -2) = 0 Reorder the terms: 5x + -2(-2 + 3x) = 0 5x + (-2 * -2 + 3x * -2) = 0 5x + (4 + -6x) = 0 Reorder the terms: 4 + 5x + -6x = 0 Combine like terms: 5x + -6x = -1x 4 + -1x = 0 Solving 4 + -1x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -1x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -1x = 0 + -4 -1x = 0 + -4 Combine like terms: 0 + -4 = -4 -1x = -4 Divide each side by '-1'. x = 4 Simplifying x = 4
| (3m+n)(m^2-n)= | | Y=(4+3k)x | | p+22=66 | | (y-2)/3+1/15(-2y-5)/3=(8-4y)/5 | | ln(x+1)=3.5 | | 6x+5y=1 | | (b/(15+8))=23 | | 4y+20= | | j+7-1=2(j-1) | | y-2/3+1/15-2y-5/3=8-4y/5 | | -17+2=x | | (3x-7)(8x+4)=0 | | 4(x-2)+x(7+5)=x(5-2)-3(6+x)+2 | | 9x-6=6x | | 13n=6-6n | | f+9=19 | | (3x-1)(8x+4)=0 | | 2b+3-3=4(b-3) | | 6v-2=5v | | 5(4x-3)=5x+30 | | p-4=(-9)+p | | 3(2z+5)=3z/4+36 | | 4w+10=2(w+10) | | 4.3x-3=3.3x | | 3*4/n=30/4 | | 2x+4=-2(0.5-x) | | 4n+20=80 | | 49-x-4=3(x-4)+1 | | 3*22/n=30/4 | | 21/2*5 | | x-8.3=-3.8 | | 2x^2-20x=-5x^2-7x-6 |